Sub-marine Continuation of Peat Deposits From a Coastal Peatland in the Southern Baltic Sea and its Holocene Development - Kreuzburg, Matthias; Ibenthal, Miriam; Janssen, Manon; Rehder, Gregor; Voss, Maren; Naumann, Michael; Feldens, Peter (Frontiers in Earth Science, 2018)
Coastal low-lying areas along the southern Baltic Sea provide good conditions for coastal peatland formation. During the Holocene, the transgression of the Littorina Sea has caused coastal flooding, submergence and erosion of ancient coastlines and former terrestrial material. The present Heiligensee & Hütelmoor peatland (located near Rostock in Northern Germany) was found to continue more than 90 m in front of the coastline based on on- and offshore sediment cores and geo-acoustic surveys. The seaward areal extent of the peatland is estimated with 0.16-0.2km2. The offshore limit of the former peatland roughly coincides with the offshore limit of a dynamic coast-parallel longshore bar, with peat deposits eroded seawards. While additional organic-rich layers were found further offshore below a small sand ridge system, no connection to the former peatlands can be established based on 14C age and C/N ratios. The preserved submerged peat deposits with organic carbon contents of 37 % in front of the coastal peatland Heiligensee & Hütelmoor was radiocarbon-dated to 6725 +/- 87 and 7024 +/-73 cal yr BP, respectively, indicating an earlier onset of the peatland as presently published. The formation time of the peat layers gives information about the local sea level rise. The local sea level curve derived from our 14C-dated organic-rich layers is in general agreement to nearby sea level reconstructions (North Rügen and Fischland, Northern Germany), with differences explained by local isostatic movements.